Drainmod Model Adaptation for Developing Recommendations Water Management in the Tertiary Block of Tidal Lowland Agriculture - Momon Sodik Imanudin; Bakri Bakri; Mustika Edi Armanto; Abdul Madjid Rohim (JOURNAL OF TROPICAL SOILS, 2021)
The primary key to successful agricultural cultivation is maintaining the groundwater level to fulfill crop water requirements, particularly during the dry season. Field study was conducted in Tidal reclamation area of section 25 at Sugihan Kanan, Bandar Jaya Village, Air Sugihan, Ogan Komering Ilir District of South Sumatra.  The DRAINMOD computer model was used to simulate water levels in dry and wet climatic conditions. The principal measured parameters are soil hydraulic conductivity and drain spacing, as well as daily rainfall data. The simulation results showed that the research area belongs to the rainfed type, and the main objective of water management is to retain water and determine some efforts to increase the groundwater level through pump irrigation in the dry season. The application of pump irrigation was applied to the plant entering the generative phase. The pump irrigation was provided to distribute water into the quarter and worm (micro) channels. The effect of this application caused the groundwater level to approach about 30 cm below the soil surface, while groundwater level in areas without pump irrigation facility was in the range of 50-60 cm. Besides efforts to increase the water table, liming is still required in order to increase production. Lime application of 1 Mg ha-1 had a significant effect on increasing production. Corn production with this treatment could produce 5 Mg ha-1, while non-treated land areas only produce 2-3 Mg ha-1.